2013
DOI: 10.1177/0018720813480177
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Eye Movements and Cognitive Workload on Lateral Position Variability in Driving

Abstract: These findings could potentially be used to identify periods of high cognitive workload during driving.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
41
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 25 publications
8
41
2
Order By: Relevance
“…A consistent effect across driving studies (Brookhuis, DeVries, & DeWaard, 1991; Cooper et al, 2013; Engstrom, Johansson, & Ostlund, 2005; Shinar et al, 2005) and in this study sample (Narad et al, 2013) was that lane position variability decreases during cell phone conversation compared with no distraction. Visual attention during conversation appears to mediate improved lateral position variability during a hands-free cell phone conversation.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…A consistent effect across driving studies (Brookhuis, DeVries, & DeWaard, 1991; Cooper et al, 2013; Engstrom, Johansson, & Ostlund, 2005; Shinar et al, 2005) and in this study sample (Narad et al, 2013) was that lane position variability decreases during cell phone conversation compared with no distraction. Visual attention during conversation appears to mediate improved lateral position variability during a hands-free cell phone conversation.…”
Section: Discussionsupporting
confidence: 69%
“…Though our findings that texting increases lane position variability and visual inattention is consistent with previous literature (Caird, Johnston, Willness, Asbridge, & Steel, 2014), our finding that visual inattention mediates the relationship between texting and increased lane variability is novel. Also, in light of Cooper et al’s (2013) finding that eye movements, much more so than cognitive load, negatively impact lane position variability, it seems that it is the act of glancing at the phone for reading and typing text and not the cognitive features of being involved in a text messaging conversation that increases lane position variability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Masson and colleagues documented the negative impact of an increased attentional load on the performance of drivers with TBI (Masson et al, 2013). Conversely, it has been shown that an increase in cognitive workload is associated with a decrease in the variability of lateral position (i.e., better vehicle control) in healthy individuals (Cooper, Medeiros-Ward, & Strayer, 2013). The impact of different levels of cognitive workload on driving performance of individuals with TBI has yet to be documented.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of any effect of secondary task complexity on SDLP was unexpected. While SDLP has typically been found to increase as a result of driver engagement in visual or physical-manual activities (Caird, Johnston, Willness, Asbridge, & Steel, 2014), other studies focusing specifically on cognitive load have shown that SDLP decreases with additional cognitive load introduced via a secondary task (Atchely & Chan, 2011;Cooper, Medeiros-Ward, & Strayer, 2013). While degrading other aspects of driving performance, the increase in cognitive demand through a secondary task has been found to afford a performance gain for SDLP potentially because participants are protecting lateral control against the risk of distraction (He, McCarley, & Kramer, 2014).…”
Section: Discussionmentioning
confidence: 99%